Theme-Based Block Play Intervention Facilitates Chinese Preschoolers’ Language Development: A Quasi-Experiment - Cai, Liman; Wu, Dandan; Zhou, Jingjing; Li, Hui (Frontiers in Psychology, 2022)
This study investigated the role of theme-based blocks play in enhancing Chinese children’s language capacity with a quasi-experiment. Altogether 61 young children were assigned to the experiment group (Mage = 5.83, SD = .25, 56.25% girls) and the control group (Mage = 5.87, SD =.28, 51.72% girls). The experiment group was engaged in a 12-week theme-based block play intervention programs, whereas the control group received no interventions but free block play during the parallel time sessions. All the children were tested with the Language Assessment for Preschool Children (LAPC) before and after the intervention. The ANCOVA results indicated that the experimental group significantly improved in LAPC test, whereas the control group showed no significant change. The educational implications of these findings are discussed.